O conhecimento prévio e a referenciação na atividade de leitura - Moreno, Teresa de Jesus Garcia (2008)
This dissertation is on the Portuguese Language Reading, Writing and Teaching research live, its topic is the production of inferences, and the problem that motivated it has its origin in the difficulties observed in the reading understanding carried out by Senior High School students. We selected, as corpus, a text by Machado de Assis, a Chronicle published in the Gazeta de Notícias newspaper on May 19th, 1888, mainly based on the activation of elements of previous knowledge that it requires from the reader. The general objective of this work is to situate the inferencial process as a process that contributes to the reading comprehension, and specifically to check what is the previous knowledge that the reader needs to activate in order to understand the analysed text, how the referencing process occurs therein, and whether recognizing the anaphoric element aids in its understanding. For its development, we based ourselves on Apothéloz, 2003; Brown & Yule, 1993; Dell΄Isola, 2001; Fávero, 2004; Kleiman, 1989; KOCH, 2004a, 2004b, 2005a, 2005b; Koch & Elias, 2006; Koch & Marcuschi, 1998; Koch & Travaglia, 1995; Marcuschi, 1985, 1999, 2001, 2005, 2007; Mondada & Dubois, 2003; Solé, 1998; Trevisan, 1992; and Van Dijk, 1984 and 1996. Thus, it is evidenced the relevance for us to act with the previous knowledge, through the knowledge about the author s life, of the knowledge about the text production context, of the knowledge about its lexicon, and of the illocutionary force, and with referencing, in order to guide the reader in the text understanding, through inferences. Finalizing the dissertation, we sought to indicate facilitating perspectives for reading teaching in Senior High School